Analisis Hukum Terkait Persetubuhan terhadap Mayat dalam Hukum Positif di Indonesia - Fajar Maulana; Rico Septian Noor; Rizki Setyobowo Sangalang; Indang Sulastri (Jurnal Hukum Lex Generalis, 2026)
Necrophilia, or sexual intercourse with corpses, presents challenges in criminal law, particularly regarding its legal regulation. This study aims to analyze the legal gaps related to necrophilia in positive law in Indonesia following the enactment of Law Number 1 of 2023 concerning the Criminal Code. The research method used is a juridical-normative approach, using a statute approach, a case approach and a concept approach. The results indicate that the Indonesian legal system lacks legal certainty regarding the rules and legal standing of perpetrators of necrophilia. Therefore, this study recommends reforming criminal law in Indonesia to provide legal certainty without diminishing humanitarian values in handling perpetrators of crimes with deviant sexual preferences.